Short term effects of air pollution on mortality in the city of Lyon, France, 1985-90. (April 1996) - Zmirou, D; Barumandzadeh, T; Balducci, F; Ritter, P; Laham, G; Ghilardi, J P
Abstract : OBJECTIVE: The short term association between daily mortality and ambient air pollution in the city of Lyon, France (population, 410, 000) between 1985 and 1990 was assessed using time series analysis. DESIGN: This study followed the standardised design and statistical analysis (Poisson regression) that characterise the APHEA project. METHODS: Four categories of cause of death were studied: total (minus external causes), respiratory, cardiovascular, and digestive causes (as a control condition). RESULTS: No association was found with any cause of death for nitrogen dioxide (NO2) and ozone (O3), nor, for any pollutant, for digestive conditions. Sulphur dioxide (SO2) and, to a much lesser degree, suspended particles (PM13), were significantly related to mortality from respiratory and cardiovascular conditions. The relative risk (RR) of respiratory deaths associated with a 50 micrograms/m3 increment of mean daily SO2 over the whole period was 1.22 (95% CI 1.05, 1.40); the RR for cardiovascular deaths was 1.54 (1.22, 1.96). The corresponding RRs for PM13 were 1.04 (1.00, 1.09) for respiratory mortality and 1.04 (0.99, 1.10) for cardiovascular deaths. CONCLUSIONS: The effects of particulates were slightly increased during the cold season. When particulates concentrations were greater than 60 micrograms/m3, the joint SO2 effect was increased, suggesting some interaction between the two pollution indicators. These results agree with other studies showing an association between particulate pollution and daily mortality; however, they also suggest the noxious effect of SO2.